INSURANCE ACTIVITIES IN THE CONDITIONS OF RUSSIAN AGGRESSION: LEGAL BASIS AND PRACTICAL PROSPECTS - Duma, Volodymyr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Aim is to study the peculiarities of the legal regulation of insurance activities in Ukraine under military situation with definition of prospects for national insurance. Research methods: general-theoretical and analytical (logical-semantic, comparative-legal, analysis and generalization) methods are used in combination with an integrated approach were used by the author. Results: it is established at the theoretical level of the study that insurance in Ukraine is possible because it is based on the national insurance law norms. Insurance in Ukraine has passed a complicated way in its development in the prewar period, and it provided the reliable legal support for insurance even during the conditions of military situation. In addition, it was found that despite the military situation, there is an opportunity for further development of insurance, in particular as an investment tool. Attracting investment opportunities of insurance companies to restore the national network of medical and pharmacy facilities destroyed by the war looks promising. It is reasonable to believe that the state can introduce new government securities, focusing, inter alia, on insurance investors, whose funds will be directed in a targeted manner to restore the national health care system. Discussion: russia’s aggression against Ukraine has led to large-scale losses of the national economy. Its restoration is an urgent task today, despite the military situation. On the other hand, it is the duty of the state to ensure the rights and freedoms of a man and citizen, in particular with regard to health care. Realization of this right has always been a costly affair, and in times of war and destruction of hundreds of health facilities, it has become much more difficult. It is impossible to solve the relevant problems only at the expense of the state, so it is reasonably to attract investment opportunities from private investors, including insurance companies. This is facilitated by the developed national insurance legislation, which allows insurers to work even in times of war.